Combined PARP14 inhibition and PD-1 blockade promotes cytotoxic T cell quiescence and modulates macrophage polarization in relapsed melanoma - Chun Wai Wong; Rotem Leshem; Kieran Neil Sefton; I-Hsuan Lin; Dervla Tamara Isaac; Mario Niepel; Adam Hurlstone (Journal for ImmunoTherapy of Cancer)
Background Programmed cell death 1 (PD-1) signaling blockade by immune checkpoint inhibitors (ICI) effectively restores immune surveillance to treat melanoma. However, chronic interferon-gamma (IFNγ)-induced immune homeostatic responses in melanoma cells contribute to immune evasion and acquired resistance to ICI. Poly ADP ribosyl polymerase 14 (PARP14), an IFNγ-responsive gene product, partially mediates IFNγ-driven resistance. PARP14 inhibition prolongs PD-1 blockade responses in preclinical models, but fails to achieve full tumor clearance, suggesting the involvement of additional resistance mechanisms.Methods We identified a robust PARP14 catalytic inhibitor gene signature and evaluated its association with patient survival. Using preclinical models and single-cell RNA sequencing, we investigated immune and tumor cell adaptations to PARP14 inhibition combined with PD-1 blockade.Results Combining PARP14 inhibition and PD-1 blockade suppressed tumor-associated macrophages while increasing proinflammatory memory macrophages. Moreover, this combination mitigated the terminal exhaustion of cytotoxic T cells by inducing a quiescent state, thereby preserving functionality. Despite the enhanced immune responses, tumor cells developed adaptive resistance by engaging alternative immune evasion pathways.Conclusions Although adaptive resistance mechanisms re-emerge, PARP14 inhibition combined with PD-1 blockade offers a promising strategy to enhance treatment outcomes and overcome ICI resistance in melanoma, as immune cells are primed for further therapeutic interventions that leverage the quiescent state.